2019
DOI: 10.1021/acs.jcim.8b00924
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Allosteric Molecular Switches of Metabotropic Glutamate Receptor 5

Abstract: The metabotropic glutamate 5 (mGlu5) receptor is a class C G protein-coupled receptor (GPCR) that is implicated in several CNS disorders making it a popular drug discovery target. Years of research have revealed allosteric mGlu5 ligands showing an unexpected complete switch in functional activity despite only small changes in their chemical structure, resulting in positive allosteric modulators (PAM) or negative allosteric modulators (NAM) for the same scaffold. Up to now, the origins of this effect are not un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…In addition, residues enclosing the allosteric site, namely, S654 3.39c and Y659 3.44c , both close to the aromatic substituent causing functional switch of the ligands, change their conformation that leads to an increased and more polar chamber. Interestingly, the role of intrahelical waters has not been investigated in the recent studies (Llinas del Torrent, Casajuana-Martin, Pardo, Tresadern, & P erez-Benito, 2019). We found that the TM bundle becomes less tightly packed and a continuous water channel is formed among the TM helices in the intracellular side below the PAM, analogously to the formation of a water channel upon activation of class A GPCRs (Angel et al, 2009;Yuan et al, 2014).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, residues enclosing the allosteric site, namely, S654 3.39c and Y659 3.44c , both close to the aromatic substituent causing functional switch of the ligands, change their conformation that leads to an increased and more polar chamber. Interestingly, the role of intrahelical waters has not been investigated in the recent studies (Llinas del Torrent, Casajuana-Martin, Pardo, Tresadern, & P erez-Benito, 2019). We found that the TM bundle becomes less tightly packed and a continuous water channel is formed among the TM helices in the intracellular side below the PAM, analogously to the formation of a water channel upon activation of class A GPCRs (Angel et al, 2009;Yuan et al, 2014).…”
Section: Resultsmentioning
confidence: 75%
“…The structural and functional importance of these interactions is underlined by several findings. The water molecule mediating the H-bond between Y659 3.44c and T781 6.46c is identified in all available X-ray structures of mGluR5-NAM complexes (Christopher et al, 2015(Christopher et al, , 2019Dor e et al, 2014) and the Hbond was also observed in MD simulations of the mGluR2 (P erez-Benito et al, 2017) and mGluR5 receptors in complex with NAMs (Llinas del Torrent, Casajuana-Martin, et al, 2019). Moreover, it was shown that mutations of Y659 3.44c and T781 6.46c in mGluR5 significantly impact the activity of allosteric ligands by either reducing (Gregory et al, 2014;Malherbe et al, 2006) or inverting (Turlington et al, 2013) their functional effect.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…by "a" according to Ballesteros-Weinstein scheme (Ballesteros and Weinstein, 1995)] for class A GPCRs or followed by "c" according to Pin et al (2003) scheme for class C GPCRs). Despite previous studies have proposed functional similarities between class A GPCR micro-switches and certain non-homologous class C GPCR residues (Perez-Benito et al, 2017; Llinas Del Torrent et al, 2019) their respective conformational changes have been observed only in MD simulations of mGlu receptor homology models, but not in mGlu receptor crystal structures (Dore et al, 2014;Christopher et al, 2015;Koehl et al, 2019) or in MD simulations starting from those (Feng et al, 2015;Dalton et al, 2017;Perez-Benito et al, 2017;Llinas Del Torrent et al, 2019). Furthermore, while the outward movement of TM6 is a hallmark of class A GPCR activation, the extent of this movement is noticeably lower in mGlu5 even when enhanced sampling methods are employed (Cong et al, 2019).…”
Section: Figure 1 | (A)mentioning
confidence: 92%
“…Significant efforts have been made to decipher the mGlu5 receptor structure-activity translation machinery (Kaae et al, 2012;Dalton et al, 2014Dalton et al, , 2017Gregory et al, 2014;Gomez-Santacana et al, 2017;Cong et al, 2019;Jojart et al, 2019;Llinas Del Torrent et al, 2019). In general, a delicate moleculargear receptor system whose mechanism of action is not yet well understood has become apparent.…”
Section: Introductionmentioning
confidence: 99%